Small and medium enterprises' innovation and product competitiveness in the Covid-19 pandemic era - Hadiah Fitriyah; Nur Ravita Hanun; Rima Azara (Universitas Muhammadiyah Magelang, 2021)
The purpose of the community service is to increase the products competitiveness of the Belimbing Wangi SMEs, Watesari Village, Balongbendo District, Sidoarjo Regency. The impact of the Covid-19 pandemic is extraordinary, especially for the Belimbing Wangi SMEs business group, where the production process and turnover has decreased, because business management is still carried out conventionally and Watesari Village tourism must be closed according to government regulations. The service method used is field observation, trial of processed star fruit products, training and assistance in processing star fruit juice, and business management training. As a result of the assistance, partners understand the importance of conducting business management and finding the best formula for star fruit juice drinks. This training also supports the sustainability of the Belimbing Wangi SMEs business and competes at the global market level.